Sovereign Encounters - Colón-Ríos, Joel I (Victoria University of Wellington Law Review, 2023)
In this article, which is an edited version of my inaugural lecture at Te Herenga Waka – Victoria University of Wellington, I argue that the concept of sovereignty is crucial to understanding one of the main questions of constitutional theory: how can constitutions facilitate self-government and, at the same time, function as mechanisms for the limitation of political power? I do so by re-examining four different ways in which I have encountered the concept of sovereignty through my academic work.